Quality and Effectiveness of Vocational Training for Adults (A Socio-Pedagogical Interpretation) - C. Katansky (University of Sofia, 2008)
Quality and effectiveness are categories which have content and meaning of their own but they belong together. In educational practice, e.g. in vocational training for adults, the quality and effectiveness are interrelated. The effectively functioning organization delivers training of good quality. The article presents a socio-pedagogical (andragogical) interpretation of the training quality and effectiveness. Their presence or absence can be judged by the indicators which are grouped as follows: training outcome; state of the process; training organization; innovation of training. With a view to these characteristics the delivery of high-quality and effective training is a complex activity. This actually means achieving and maintaining a balance between the above mentioned indicators.